Metal-free electrochemical oxidative trifluoromethylation/C(sp2)H functionalization of quinolinones. Issue 35 (27th August 2020) - Xu, Chunzhao; Liu, Yue; Liu, Hao; Ma, Junjie; He, Xin; Wu, Hongfeng; Li, Yuqin; Sun, Zhizhong; Chu, Wenyi
Graphical abstract: An electrochemical oxidation direct trifluoromethylation of quinolinone derivatives under metal-free catalysis was developed. The reaction mechanism is proposed and proved by cyclic voltammetry (CV), control experiments and radical captured experiments. Highlights: Metal-free and oxidant-free conditions to afford 3-trifluoromethyl quinolinones. First direct trifluoromethylation of 2-phenylquinoline-4(1 H )-one. First to obtain BHT-CF3 adduct confirmed the radical mechanism. High functional group tolerance and scalability. Abstract: Electrochemical direct trifluoromethylation of quinolinones was described under metal-free catalysis and oxidant-free conditions. A series of 2-aryl-3-trifluoromethylquinoline-4(1 H )-ones were obtained in medium to good yield by using the method. By using butylated hydroxytoluene (BHT) as free radical blocker, adduct of BHT-CF3 was originally captured, which confirmed that the reaction was a free radical mechanism. Based on the results of capturing radical and cyclic voltammetry (CV), a reaction mechanism was proposed.